Additional diagnostic capabilities in the practice of a PAP-test using liquid-based cytology - Artem K. Aksamentov (Eco-vector, 2021)
The role of oncogenic strains of human papillomavirus in the development of cervical cancer is currently not in doubt. In cervical cancer screening, a co-testing strategy is used, in which cytology and HPV testing are performed. When performing a cytological examination by liquid-based cytology, it is possible to conduct additional diagnostic studies that can be used to more effectively sort patients in order to optimize the volume of diagnostic and therapeutic measures. The article highlights the possibilities of diagnostic tests based on the assessment of microRNA and mRNA expression, as well as tests based on the analysis of DNA methylation from the cytological material. The introduction of new molecular genetic predictors of the cervical cancer development into clinical practice can increase the effectiveness of currently used screening programs.